2022
DOI: 10.11611/yead.1076897
|View full text |Cite
|
Sign up to set email alerts
|

Sovereign Credit Default Swap (Cds) Spreads Changes in Various Economic Conjunctures: Evidence From Turkey by Machine Learning Algorithms

Abstract: The study aims to define the sources of Turkey's sovereign CDS spread changes to develop policies that stabilize CDS spreads since they have a volatile and increasing trend, especially in the last two years.In this context, monthly data of 13 factors related to international, macroeconomic, and market between 2011/1 and 2019/12 are used by dividing the dataset into three periods as the full period (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019), the stability period (2011)(2012)(2013)(2014)(2015)(2016)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…These results emphasize the significance of reserves as a determinant of changes in Sovereign CDS Term Premium in the examined countries. These findings align with the research conducted by Kartal et al (2022) andRathi et al (2022), which similarly indicated a negative impact of changes in reserves on CDS spread, implying that an increase in reserves reduces sovereign risk spread. 7 displays the outcomes of MIDAS regression, investigating the relationship between Sovereign CDS Term Premium and terms of trade for the countries in the sample.…”
Section: Resultssupporting
confidence: 91%
“…These results emphasize the significance of reserves as a determinant of changes in Sovereign CDS Term Premium in the examined countries. These findings align with the research conducted by Kartal et al (2022) andRathi et al (2022), which similarly indicated a negative impact of changes in reserves on CDS spread, implying that an increase in reserves reduces sovereign risk spread. 7 displays the outcomes of MIDAS regression, investigating the relationship between Sovereign CDS Term Premium and terms of trade for the countries in the sample.…”
Section: Resultssupporting
confidence: 91%
“…Based on the empirical findings, the results confirm the hypotheses, which are examined in the study. The outcomes of the study are generally consistent with the studies [ 10 , 11 , 27 ] for CDS [ 12 , 31 ], for FX, and [ [13] , [14] , [15] , [16] , 19 , 24 , 26 , 27 ] for CBR. Hence, the results are important because they provide details regarding the dynamic link between CBR, CDS spreads, and USD/TRY in Turkey.…”
Section: Discussionsupporting
confidence: 83%
“…Economic growth, inflation, interest rates, credit/deposit ratio, credit growth, non-performing loans, stock market indices, and unemployment are typical examples of these macroeconomic and financial indicators [ [5] , [6] , [7] , [8] , [9] ]. Although there are many indicators, CBR, CDS spreads, and FX rates are the ones, which are the most important indicators reflecting the soundness, riskiness, vulnerability, and predictability of countries [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation